HUBUNGAN PERAN KEKUATAN KARAKTER DENGAN RESILIENSI PERAWAT DI RUMAH SAKIT GUNUNG MARIA TOMOHON - Marsel Paendong; Andi Buanasari; Dina Mariana (JURNAL KEPERAWATAN, 2022)
Background: Work Stress due to a high workload on Nurses is the impact of the low a nurse resilience behavior. The role of the character power from each nurse can be built and improved by a nurse resilience behavior, so that a nurse can be endured and able to face all the challenges or work stress that they are facing. Aim : this research aimed to know the correlation between the character strength and the nurse resilience at Gunung Maria Hospital of Tomohon. Method: This research used quantitative method with cross sectional approach, 154 respondents were invloved in this study through purposive sampling technique. The data were analyzed using the spearman rank correlations test. Results : There was a significant correlation between the role of character strength and the resilience of nurses at Gunung Maria Hospital (p=0,000) with coefficien tcorrelation = 0.297 which means the correlation between two variables was sufficient and has a positive direction, that means the higher the character strength role score. The higher the resilience score. Conclusion : There was a sufficient correlation between the role of character strength and the resilience of nurses at Gunung Maria Hospital. It is important for the nurses Â to improve their role of character strength in building resilience.Keywords : Character Strengths; Nurses' Resilience; Clinical Nurses